2014
DOI: 10.20344/amp.4966
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of QT Intervals During Diagnosis and After Follow-Up in Acromegaly Patients

Abstract: Introduction: It was aimed to calculate QT intervals in patients with acromegaly and to reveal its correlation between QT intervals, and growth hormone and insulin like growth factor-1. Material and Methods: Forty-one patients with acromegaly were enrolled into the study. Another 41 individuals with similar features, such as comorbid diseases, age and sex constituted the control group. The electrocardiographies of patients with acromegaly were evaluated at the baseline and after the follow-up. Only one electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 22 publications
2
14
2
1
Order By: Relevance
“…In the current study, we assess association of QTc with these clinical and echocardiographic variables. Previous studies have reported no relationship between GH/IGF-1 levels and QTc (12,19,24). However, we found signi cant positive relationship between GH level and QTc.…”
Section: Correlation Analysis Between Clinical Features and Qtc In Ac...contrasting
confidence: 66%
See 3 more Smart Citations
“…In the current study, we assess association of QTc with these clinical and echocardiographic variables. Previous studies have reported no relationship between GH/IGF-1 levels and QTc (12,19,24). However, we found signi cant positive relationship between GH level and QTc.…”
Section: Correlation Analysis Between Clinical Features and Qtc In Ac...contrasting
confidence: 66%
“…Fatti et al have reported QTc signi cantly reduced in acromegalic patients with primary somatostatin analogues therapy (12). Recently, acromegalic patients with surgery was also found have statistically signi cant improvement QTc (19). These studies suggested effective therapy can decrease the risk of ventricular arrhythmias in acromegaly.…”
Section: Correlation Analysis Between Clinical Features and Qtc In Ac...mentioning
confidence: 94%
See 2 more Smart Citations
“…Τα τελευταία χρόνια, πολυάριθμες μελέτες σε ασθενείς με υπερέκκριση GH (μεγαλακρία), καθώς και σε ασθενείς με ανεπάρκεια GH, προβάλλουν το ρόλο της GH στα καρδιαγγειακά νοσήματα. Συγκεκριμένα, τόσο η υπερέκκριση όσο και η ανεπάρκεια της αυξητικής ορμόνης έχουν συσχετισθεί με αυξημένη καρδιαγγειακή θνητότητα ([110],[111]). ΜεγαλακρίαΗ πρώτη παρατήρηση σε ασθενείς με μεγαλακρία έγινε το 1895 από τον Huchard, ο οποίος περιέγραψε στη Journal de Practiciens 3 αυτοψίες ασθενών και συσχέτισε την καρδιακή δυσλειτουργία με τη μεγαλακρία[112].Το επιστημονικό ενδιαφέρον για την καρδιαγγειακή συν-νοσηρότητα στους ασθενείς με μεγαλακρία εντάθηκε τις επόμενες ΚΕΦΑΛΑΙΟ 1: ΓΕΝΙΚΟ ΜΕΡΟΣ ΕΠΙΔΡΑΣΗ ΑΥΞΗΤΙΚΩΝ ΠΑΡΑΓΟΝΤΩΝ ΠΡΟΣΔΕΜΕΝΩΝ ΣΕ ΒΙΟΛΟΓΙΚΟ ΙΚΡΙΩΜΑ ΣΤΗ ΜΕΤΕΜΦΡΑΓΜΑΤΙΚΗ ΑΡΡΥΘΜΙΟΓΕΝΕΣΗ | 87 δεκαετίες, με αποκορύφωμα τα τελευταία 30 έτη, οπότε και άρχισε να αναδεικνύεται ο ρόλος της GH σε αυτή.…”
unclassified